Unlocking Potential: How the RADEC Model and Motivation Transform Expository Narrative Essay Writing - Lina Marcelina; Elfia Sukma; Fetri Yeni J; Yuli Tiarina; Dary Nasmi Fauziah (International Journal of Elementary Education, 2025)
This study aims to analyze the effect of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model and learning motivation on the expository narrative writing skills of fourth-grade elementary school students. This research employed an experimental method with a quasi-experimental design using a 2x2 factorial pattern. The population consisted of all fourth-grade students at elementary schools in Cluster VI, during the 2023/2024 academic year. The research instruments included a learning motivation questionnaire and a test of expository narrative writing skills. The results revealed that: (1) the RADEC learning model had a significant effect on students’ expository narrative writing skills; (2) the RADEC model positively influenced the writing skills of students with high learning motivation; (3) the RADEC model did not significantly affect the writing skills of students with low learning motivation; and (4) there was no interaction between the RADEC learning model and learning motivation in influencing expository narrative writing skills. These findings indicate that the RADEC model is effective in improving students’ writing abilities, particularly among those with high learning motivation.